RANCANG BANGUN SISTEM STABILISASI SUHU PENGGORENGAN BERBASIS IOT - Karin, Karina Zaruska; Azhari, Muhamad; Sulistyo, Eko; Febriansyah, Aan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
In Bangka Belitung, there’s many UMKM produce souvenirs typical of Bangka Belitung such as kemplang, kretek, crackers, etc. However,the frying technique used by UMKM from the results of visits mostly still uses the manual method, such as UMKM cannot monitor frying temperatures during production and also cannot control them. UMKM in controlling the temperature still use the manual method,namely if the temperature of the oil has started to heat up and the product started to brown,the stove knob is reduced and otherwise if the temperature isn’t hot enough,the stove knob will be raised.However,UMKM can’t detect the temperature used at that time,causing many production defects.From the results that has been carried out in UMKM, technology is needed to stabilize the temperature of the frying pan so that the production results produce the appropriate product. For the implementation of this frying stabilization process using microkontroller technology,where the actuator use servo motor that’s controlled to the stove.While the control process uses fuzzy logic,where the input and output will be set according to the rule base(rules defined according to the frying conditions in UMKM).The average percentage error from the test results of the frying temperature sensor with low input is 6.50%,medium input is 0.74%,and high input is 1.70%.